1996
DOI: 10.1300/j082v31n01_10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Homosexual Imagery in Advertising on Attitude Toward the Ad

Abstract: This study examines the differential impact that images in magazine advertising suggestive of either homosexuality or heterosexuality have on attitude toward the ad. Results support the hypothesis that homosexual imagery in advertising led to more positive attitude toward the ad among viewers more tolerant of homosexuality than among those less tolerant of homosexuality. Surprisingly, ads with heterosexual imagery were rated less favorably by viewers tolerant of homosexuality than by those less tolerant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
0
28
0
3
Order By: Relevance
“…Thus, these individuals will exhibit a level of in-group favoritism toward homosexual imagery in advertisements. Looking at both heterosexuals and homosexuals from an in-group/out-group perspective, Bhat et al (1996) found that gay consumers have more favorable emotional and attitudinal responses to advertisements depicting a gay male couple than to advertisements depicting a heterosexual couple. Thus, it stands to reason that more gay-themed ads will be more likely placed in gay-targeted magazines than in nongay themed ads.…”
Section: Social Identity and Social Identity Theory And Social Adaptamentioning
confidence: 99%
“…Thus, these individuals will exhibit a level of in-group favoritism toward homosexual imagery in advertisements. Looking at both heterosexuals and homosexuals from an in-group/out-group perspective, Bhat et al (1996) found that gay consumers have more favorable emotional and attitudinal responses to advertisements depicting a gay male couple than to advertisements depicting a heterosexual couple. Thus, it stands to reason that more gay-themed ads will be more likely placed in gay-targeted magazines than in nongay themed ads.…”
Section: Social Identity and Social Identity Theory And Social Adaptamentioning
confidence: 99%
“…Companies such as Sony, Apple, American Express, Toyota, Microsoft, IKEA and the alcohol brands of Carillon Importers (e.g. Absolute, Bombay Sapphire) featured homosexual imagery in their advertisements (Bhat, Leigh andWardlow 1996, 1998). Moreover, gay celebrities appeared in advertisements and some fashion magazines such as Esquire and GQ (Elliott, 1992(Elliott, , 1995(Elliott, , 2000.…”
Section: Brief Overview Of Use Of Gay/lesbian Images In Advertisingmentioning
confidence: 99%
“…Moreover, gay celebrities appeared in advertisements and some fashion magazines such as Esquire and GQ (Elliott, 1992(Elliott, , 1995(Elliott, , 2000. Some businesses specifically targeted gay consumers (Bhat et al 1996) as evidenced by increases in advertising spending (e.g. increased from $61.6 million in 1995 to $155.3 million in 1999) in gay publications ('Spending increases in gay magazines ' 2000).…”
Section: Brief Overview Of Use Of Gay/lesbian Images In Advertisingmentioning
confidence: 99%
“…Desta forma, a homossexualidade pode ser definida tanto pelo comportamento sexual do sujeito, pelos seus sentimentos de atração com relação a pessoas do mesmo sexo biológico ou por autoidentificação (o sujeito se vê como homossexual). Assim, podemos dizer que estes instrumentos acabam sendo prejudicados, dentre outros motivos, pela falta de rigor dos termos científicos empregados (Bhat, Leigh & Wardlow, 1996;Badgett & King, 1997). Além disso, tanto nos Estados Unidos como no Brasil, não existem pesquisas ou dados demográficos oficiais sobre a população homossexual, o que faz com que as informações disponíveis sobre estes indivíduos sejam incompletas, no que diz respeito à caracterização das mesmas.…”
Section: Aferição E Desenvolvimento Do Preconceito Internalizadounclassified